A DEBATE BETWEEN A THEIST AND A SANTA CLAUSIST (ACT II). Issue 40 (9th April 2015) - Tallman, Ruth; Johnson, David Kyle
Abstract : In Act I, Faith and Klaus had it out regarding whether their deity of choice – God and Santa respectively – exists. Although Klaus was unable to convince Faith, Klaus suggested that Krampus, his 'Santa pastor' (the guy who owns the mall where he buys his Christmas presents), will set Faith straight. We join the dialogue, once again, as Faith is about to first meet Krampus, who promises to provide us with more sophisticated arguments in favor of Santa Claus.